Longitudinal Change in Bone Density, Geometry, and Estimated Bone Strength in Older Men and Women From The Gambia: Findings From the Gambian Bone and Muscle Aging Study (GamBAS). (11th November 2022) - Ó Breasail, Mícheál; Pearse, Camille; Zengin, Ayse; Jarjou, Landing; Cooper, Cyrus; Ebeling, Peter R; Prentice, Ann; Ward, Kate A
ABSTRACT: Musculoskeletal aging in the most resource‐limited countries has not been quantified, and longitudinal data are urgently needed to inform policy. The aim of this prospective study was to describe musculoskeletal aging in Gambian adults. A total of 488 participants were recruited stratified by sex and 5‐year age band (aged 40 years and older); 386 attended follow‐up 1.7 years later. Outcomes were dual‐energy X‐ray absorptiometry (DXA) ( n = 383) total hip areal bone mineral density (aBMD), bone mineral content (BMC), bone area (BA); peripheral quantitative computed tomography (pQCT) diaphyseal and epiphyseal radius and tibia ( n = 313) total volumetric BMD (vBMD), trabecular vBMD, estimated bone strength indices (BSIc), cross‐sectional area (CSA), BMC, and cortical vBMD. Mean annualized percentage change in bone outcomes was assessed in 10‐year age bands and linear trends for age assessed. Bone turnover markers, parathyroid hormone (PTH), and 25‐hydroxyvitamin D (25(OH)D) were explored as predictors of change in bone. Bone loss was observed at all sites, with an annual loss of total hip aBMD of 1.2% in women after age 50 years and in men at age 70 years plus. Greater loss in vBMD and BSIc was found at the radius in both men and women; strength was reduced by 4% per year in women and 3% per year in men ( p trend 0.02, 0.03, respectively). At cortical sites, reductions in BMC, CSA, and vBMD were observed, being greatest in BMC in women, between 1.4% and 2.0% per annum. Higher CTX and PINP predicted greater loss of trabecular vBMD in women and BMC in men at the radius, and higher 25(OH)D with less loss of tibial trabecular vBMD and CSA in women. The magnitude of bone loss was like those reported in countries where fragility fracture rates are much higher. Given the predicted rise in fracture rates in resource‐poor countries such as The Gambia, these data provide important insights into musculoskeletal health in this population. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).